Breastfeeding rates in China: a cross-sectional survey and estimate of benefits of improvement. (October 2016) - Yang, Zhenyu; Lai, Jianqiang; Yu, Dongmei; Duan, Yifan; Pang, Xuehong; Jiang, Shan; Bi, Ye; Wang, Jie; Zhao, Liyun; Yin, Shian
Abstract: Background: Breastfeeding is the gold standard for infant and young child feeding. Increased rates of breastfeeding could reduce morbidity and mortality for both children and mothers. In addition, breastfed children could have better cognitive development, persisting through later life. However, quantitative data are scarce on the effect of improved breastfeeding rates in China. The objectives of this study were to assess current breastfeeding rates and to analyse the potential effect of improved breastfeeding rates in China. Methods: A national representative survey (Chinese Nutrition and Health Surveillance) of children ages 6 years was done in 2013. Stratified multistage cluster sampling was used to select study patricipants. WHO infant and young feeding indicators were used to assess breastfeeding practice. Lives Saved Tool (version 5·441) was used to estimate death prevented with improved breastfeeding practice. The survey was approved by the National Institute for Nutrition and Health, Chinese Center for Disease Control and Prevention Medical Ethnical Committee. All caregivers signed the consent form. Findings: 14 539 children aged 2 years and younger (0–730 days) were studied from 55 counties in 30 provinces in China. The weighted prevalence for ever breastfed was 79·6%; 20·8% were exclusively breastfed at 6 months, 11·5% were breastfed at 1 year of age, and 6·9% were breastfed at 2 years of age. The median duration of breastfeeding was 8·63 months. Assuming an increase to 50% exclusively breastfed infants at 6 months, the Lives Saved Tool predicted 19 323 (11 266–22 530) fewer deaths and a reduction in mortality of 5% (from 10·7 per 1000 to 10·17 per 1000) among children under 5 years of age. Interpretation: The rates of breastfeeding in China are low. Improved breastfeeding rates could be substantially reduce mortality in children aged 5 years and younger in China. Funding: Chinese Central Government